Response of Sesbania (Sesbania sesban L. Merr.) to inoculation with indigenous isolates of Rhizobium strains - Woldemeskel, Endalkachew; Dogiso, E.; Haile, Wassie (Academic Journals, 2016)
Nitrogen fixation through legume-rhizobium symbiosis serves as a cost effective, sustainable and ecofriendly source of N to fodder and grain legume crops. However, there is a need to identify effective rhizobial inoculants compatible with a particular legume. An experiment was conducted to evaluate the effectiveness of forty indigenous isolates of Rhizobium strains on Sesbania sesban L. Merr. Each strain was cultured in yeast manitol broth for 3-5 days and inoculated to sesbania seedlings. Unfertilized (-N) and N fertilized (+N) treatments were also included as control treatments. Results revealed that Rhizobium strains have significantly affected nodulation, growth and N content (NC) of sesbania. Based on their relative effectiveness on seedling growth of sesbania, the test strains were grouped into six clusters. Eight strains (20%) in clusters VI, V and VI produced significantly higher nodulation, growth and NC on seedlings of sesbania than those produced by all other strains and +N treatment. On average, these strains increased shoot dry matter and NC by 50 and 50.8 % over +N treatments, respectively. Their mean symbiotic effectiveness (SE) values were > 85 % and hence are classified as highly efficient strains. In conclusion, there is a significant possibility of being able to isolate effective strains, which can be used as inoculants for sesbania, from rhizobial biodiversity resources in Ethiopian soils.